THEORY, PRACTICE, AND PARENTAL ASPIRATIONS: AN ANALYSIS OF TEACHING AND LEARNING IN MALAYSIAN CHILDCARE CENTRES (TASKA) - NURUL SYAFIQAH ZAIDIN; MOHD NAZRI ABDUL RAHMAN (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
This study analyzes the teaching and learning approaches used in Malaysian Childcare Centres (TASKA) to determine their effectiveness in meeting the increasingly high expectations of modern parents regarding children aged 0 to 4. Drawing on established developmental frameworks, the research employed a Systematic Literature Review (SLR) to synthesize findings on core strategies, including Learning Through Play and Positive Parenting Styles. Results confirm a strong conceptual alignment between TASKA principles and parental demands for character development and early cognitive preparation. However, implementation is hindered by two critical gaps: a persistent educator competency deficit in applying diverse methods like the Thematic Approach, and a pervasive parental involvement gap caused by busy modern lifestyles. The study concludes that addressing these barriers through continuous training and digital collaboration is essential for optimizing TASKA quality.